Modern Living “hewn out of the unknown wilderness”: Aluminum, City Planning, and Alcan’s British Columbian Industrial Town of Kitimat in the 1950s - Cross, Brad (Urban History Review / Revue d'histoire urbaine, 2016)
As a new town on the Northern British Columbian frontier, Kitimat represented mid-twentieth-century ideas of industrial resource development and town planning. Alcan executives saw Kitimat’s town design as crucial to the recruitment and retention of a workforce for its megaproject of the 1950s and 1960s, which became the crown jewel of its global enterprise. The combination of high-tech aluminum production and town planning techniques promised employees a family-oriented lifestyle in a state-of-the-art town. Kitimat spearheaded this push for a new kind of frontier experience.